2020
DOI: 10.1080/01480545.2020.1769642
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenotoxic evaluation of the acetonitrile extract, citrinin and dicitrinin-A from Penicillium citrinum

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…[ 208 ], citrinin (CIT) and dicitrinin-A from Penicillium c . [ 209 ], allantopyrone E from Aspergillus v . [ 210 ], integracin A and B from Cytospora spp.…”
Section: Anticancer Activity Of Endophytic Fungimentioning
confidence: 99%
“…[ 208 ], citrinin (CIT) and dicitrinin-A from Penicillium c . [ 209 ], allantopyrone E from Aspergillus v . [ 210 ], integracin A and B from Cytospora spp.…”
Section: Anticancer Activity Of Endophytic Fungimentioning
confidence: 99%
“…In another study using yeast cells, CIT (400 µg/mL) induced the strong expression of 68 genes related to oxidative stress, suggesting toxicity triggered by CIT at high concentrations [ 64 ]. De Oliveira-Filho and collaborators [ 65 ] observed that citrinin can exert its toxic, cytotoxic, and mutagenic effects in yeast strains, possibly through oxidative stress induction. CIT’s cytotoxicity can be attributed to its role as an apoptosis inducer.…”
Section: Discussionmentioning
confidence: 99%
“…MpPhy , a gene encoding the photosensitive pigment phytochrome, is closely related to the growth of Monascus and the synthesis of secondary metabolites, such as CIT. , According to Zhang et al, CIT production in Monascus significantly decreases during liquid fermentation when exposed to blue light, and catalase activity also shows a consistent pattern. Its substrate, hydrogen peroxide, degrades CIT, suggesting that blue light may alter the metabolic pathway in Monascus , thereby controlling CIT . Yang et al.…”
Section: Control Of Cit Contamination In Cheese Productsmentioning
confidence: 99%
“…Its substrate, hydrogen peroxide, degrades CIT, suggesting that blue light may alter the metabolic pathway in Monascus, thereby controlling CIT. 140 Yang et al investigated the molecular mechanism of blue light on CIT and discovered a long noncoding RNA called AOANCR, which does not encode protein, however, it plays an important regulatory role in physiological and metabolic processes. 141 Additionally, Wang et not have a significant impact on CIT synthesis, and with the increase in light source intensity, an inhibitory effect began to appear, while low-intensity green light showed different effects that could stimulate CIT production.…”
Section: Use Of Essential Oilsmentioning
confidence: 99%